N-3-Oxo-Octanoyl Homoserine Lactone Primes Plant Resistance Against Necrotrophic Pathogen Pectobacterium carotovorum by Coordinating Jasmonic Acid and Auxin-Signaling Pathways - Liu, Fang; Zhao, Qian; Jia, Zhenhua; Zhang, Siyuan; Wang, Juan; Song, Shuishan; Jia, Yantao (Frontiers in Plant Science, 2022)
Many Gram-negative bacteria use small signal molecules, such as N-acyl-homoserine lactones (AHLs), to communicate with each other and to coordinate their collective behaviors. Recently, increasing evidence has demonstrated that long-chained quorum sensing signals play roles in priming defense responses in plants. Our previous work indicated that a short-chained signal, N-3-oxo-octanoyl homoserine lactone (3OC8-HSL), enhanced Arabidopsis resistance to the hemi-biotrophic bacteria Pseudomonas syringae pv. tomato DC3000 through priming the salicylic acid (SA) pathway. Here, we found that 3OC8-HSL could also prime resistance to the necrotrophic bacterium Pectobacterium carotovorum ssp. carotovorum (Pcc) through the jasmonic acid (JA) pathway, and dependent on auxin responses, in both Chinese cabbage and Arabidopsis. The subsequent Pcc invasion triggered JA accumulation and increased the down-stream genes expressions of JA synthesis genes (LOX, AOS and AOC) and JA response genes (PDF1.2 and VSP2). The primed state was not observed in the Arabidopsis coi1-1 and jar1-1 mutants, which indicated that the primed resistance to Pcc was dependent on the JA pathway. The 3OC8-HSL was not transmitted from roots to leaves, and it induced indoleacetic acid (IAA) accumulation and the DR5 and SAUR auxin-responsive genes’s expressions in seedlings. When Arabidopsis and Chinese cabbage roots were pretreated with exogenous IAA (10 μM), the plants had activated JA pathway and enhanced resistance to Pcc, which implied that the JA pathway was involved in AHL priming by coordinating with the auxin pathway. Our findings provide a new strategy for the prevention and control of soft rot in Chinese cabbage, and provide theoretical support for use of the quorum-sensing AHL signal molecules as a new elicitor.